Impact of Augmented Reality-Based Interactive Worksheets on Student Achievement in Chemical Equilibrium - Khairunisa, Dira; Nurfajriani, Nurfajriani (Pendidikan Kimia FKIP Universitas Jambi, 2025)
Low student achievement in chemistry is often linked to difficulties in understanding abstract concepts, particularly when instructional media lack interactivity and variation. This study aims to investigate the effect of using augmented reality (AR)-based interactive student worksheets (LKPD) on students’ learning outcomes in the topic of chemical equilibrium. The research employed a quasi-experimental design, specifically the nonequivalent control group design. The sample consisted of 72 students from class XI at a senior high school, divided into two groups: XI-F1 G (experimental group) and XI-F1 F (control group), each comprising 36 students. A multiple-choice test consisting of 20 items was used as the research instrument to measure students' learning outcomes. The data were analyzed using SPSS version 25, and the hypothesis was tested through an independent samples t-test at a significance level of 0.05. The results showed a Sig. (2-tailed) value of 0.001, which is less than α = 0.05, indicating a statistically significant difference between the two groups. Based on these findings, it can be concluded that the use of interactive LKPD integrated with augmented reality media has a significant positive effect on students’ learning outcomes in chemical equilibrium. Keyword: Augmented Reality, Learning Outcomes, student worksheets